The Effect of Blended Learning on Nursing Students’ Knowledge - Ni Gusti Ayu Eka; Grace Solely Houghty; Juniarta Juniarta (Universitas Airlangga, 2019)
Introduction: Blended learning is assumed to improve the students’ understanding of learning at nursing school especially in the current industrial revolution 4.0 era. The combination of classroom and online activities is expected to provide better study outcomes. This research aimed to compare the knowledge scores of the nursing students in blended learning concerning a research and statistics course at a private faculty of nursing.Methods: The knowledge scores resulted from the student’s score in their mid and final examinations (0-100). A total of 474 respondents who were third year students involved in the study. This study applied a pre-experimental design. Due to the data having a significant non-normal value (p value < 0.001), this study further compared the mean-rank of the students’ score using a Wilcoxon test analysis.Results: The results of this study revealed that there was a significant difference (p value < 0.0001) between the students’ score in the mid (Median 72.5; SD 9.82) and final exam examinations (Median 86.66; SD 4.75). This means that the students had a better score in their final exam.Conclusion: Applying a blended learning method was a positive experience for the nursing students in terms of knowledge. It is needed to explore the students’ understanding and interest in their learning process using blended learning.